2016
DOI: 10.1016/j.actamat.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a twinning–detwinning process in wrought Mg alloys by the acoustic emission technique

Abstract: Two extruded magnesium alloys, AZ31 with a bimodal microstructure and ZE10 with a homogeneous microstructure, were pre-compressed and subsequently subjected to tensile loading. The acoustic emission (AE) technique was concurrently applied to determine the activity of particular deformation mechanisms. Significant changes in the AE response were correlated with the inflection points on the tensile curve. Twinning and detwinning processes were analyzed using the AE dataset. Particularly, nucleation of various ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…The AE energy also drops at the point of loading reversal and remains low as long as the de-twinning process is active on the tensile part of each cycle. This finding is close to the results reported in [32,54,59], where it was argued that the de-twinning process, which is systematically observed at strain path reversal in Mg polycrystals, proceeds at the velocities much slower than those at twin nucleation and is not directly detectable by AE. This can be clearly seen on the enlarged fragment of the AE time-series shown in Figure 5b.…”
Section: Resultssupporting
confidence: 78%
“…The AE energy also drops at the point of loading reversal and remains low as long as the de-twinning process is active on the tensile part of each cycle. This finding is close to the results reported in [32,54,59], where it was argued that the de-twinning process, which is systematically observed at strain path reversal in Mg polycrystals, proceeds at the velocities much slower than those at twin nucleation and is not directly detectable by AE. This can be clearly seen on the enlarged fragment of the AE time-series shown in Figure 5b.…”
Section: Resultssupporting
confidence: 78%
“…On reversal of the strain paths, the twins formed during pre-straining tend to detwin as lower stresses are required for detwinning as compared to twin propagation. Similar works [18,19] have shown that detwinning via atomic shuffling occurs as a consequence of strain path changes.…”
mentioning
confidence: 53%
“…The findings discussed above lay an important insight for quantifying the influence of deformation rate on stress-triaxiality. Previously detwinning in the literature has been strongly credited to pure atomic shuffling [17][18][19]. Proust et al [17], have shown that detwinning occurs in the case of specimens subjected to strain path changes along the rolling direction (RD) or extruded direction (ED).…”
mentioning
confidence: 99%
“…Recently the grain size dependence of twinning has been documented; twins first occur in larger grains and with a progress of plastic deformation they can be activated also in smaller grains. [3,[21][22][23] Hence, in all investigated alloys, twins form preferentially in the unrecrystallized grains. The presence of the LPSO phase may inhibit or delay twinning activity due to a high density of stacking faults enriched with Zn/Y in the basal planes.…”
Section: Discussionmentioning
confidence: 99%